2007
DOI: 10.1159/000101068
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone and Receptor Distributions in the Visual Processing Regions of Four Coral Reef Fishes

Abstract: Gonadotropin-releasing hormone (GnRH) is widely distributed in the brain of fishes where it may function as a neuromodulator of sensory processing and behavior. Immunocytochemical and neuronal label experiments were conducted on species from four families of coral reef fishes (Chaetodontidae, butterflyfish; Pomacentridae, damselfish; Gobiidae, goby; and Labridae, wrasse) to assess conservation of GnRH targets in the visual processing retina and brain. In all species, GnRH-immunoreactive (-ir) axons from the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 144 publications
(150 reference statements)
2
10
0
1
Order By: Relevance
“…There are even fewer functional studies of the teleost POA (or other brain areas) in regards to sexually motivated behavior (but see below and discussion on vocal fishes). AVT-ir and GnRH-ir and/or their receptors are also found in peripheral sensory organs and central sensory processing areas (Dewan et al, 2008; Foran et al, 1997; Goodson and Bass, 2000b; Grens et al, 2005; Maruska, 2009; Maruska and Fernald, 2010; Maruska and Tricas, 2007; Stell et al, 1987), implicating the role of these neuropeptides in modulating levels of “sensory responsiveness”.…”
Section: What Is Known Of the Neural Circuitry Of “Sexual Arousal” Inmentioning
confidence: 99%
“…There are even fewer functional studies of the teleost POA (or other brain areas) in regards to sexually motivated behavior (but see below and discussion on vocal fishes). AVT-ir and GnRH-ir and/or their receptors are also found in peripheral sensory organs and central sensory processing areas (Dewan et al, 2008; Foran et al, 1997; Goodson and Bass, 2000b; Grens et al, 2005; Maruska, 2009; Maruska and Fernald, 2010; Maruska and Tricas, 2007; Stell et al, 1987), implicating the role of these neuropeptides in modulating levels of “sensory responsiveness”.…”
Section: What Is Known Of the Neural Circuitry Of “Sexual Arousal” Inmentioning
confidence: 99%
“…Recent evidence reported that class 1 GnRHR is indeed expressed in retinal amacrine cells of the teleost Astatotilapia ( Haplochromis) burtoni whereas class 2 GnRHR is expressed in the ganglion cell layer [45]. Also, GnRHR was identified in the retina of four coral reef fishes [46]. In mammals, data are extremely scarce and result from isolated observations in a small number of species like rhesus macaque, opossum, vole, bat and rat [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…But how does the GnRH peptide that is released from these neurons modulate the information processing of target neurons to control reproduction, especially reproductive behaviors? Recently, many researchers are interested in the forebrain olfactory and visual systems as target systems of GnRH neuromodulation because of the projection of TN-GnRH3 neurons [4,37,[42][43][44] and localization of GnRH receptors [16][17][18].…”
Section: Gnrh Peptides Modulate Sensory Information Processing Dependmentioning
confidence: 99%
“…The axons of TN-GnRH3 neurons innervate the retina and optic tectum [42,44,51]. GnRH positively modulates the efficiency of synaptic transmission from the retinal efferent axons to the periventricular neurons of the optic tectum in the rainbow trout [52].…”
Section: Gnrh Peptides Modulate Sensory Information Processing Dependmentioning
confidence: 99%